2004
DOI: 10.1093/ansci/82.4.1062
|View full text |Cite
|
Sign up to set email alerts
|

Copper proteinate in weanling pig diets for enhancing growth performance and reducing fecal copper excretion compared with copper sulfate1

Abstract: Two 28-d experiments were conducted to evaluate the efficacy of low dietary concentrations of Cu as Cu-proteinate compared with 250 ppm Cu as CuSO4 with growth performance, plasma Cu concentrations, and Cu balance of weanling swine as the criteria. In the production study (Exp. 1), 240 crossbred pigs that averaged 19.8 d of age and 6.31 kg BW initially were group-fed (two or three pigs per pen) the basal diets (Phase 1: d 0 to 14 and Phase 2: d 14 to 28) supplemented with 0 (control), 25, 50, 100, or 200 ppm C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
31
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 14 publications
10
31
1
3
Order By: Relevance
“…The same was shown by Wedekind et al (1994) in metacarpals and coccigea vertebrae of pigs that received higher Zn supplementation in diet. Studies comparing organic and inorganic sources of Cu showed an increased uptake and retention of Cu in pigs fed organic source (Coffey et al 1994, Veum et al 2004), which was not observed in the present study for Fe, Cu, and Zn content in bones.…”
Section: Mineral Retention In Metacarpals and Livercontrasting
confidence: 86%
“…The same was shown by Wedekind et al (1994) in metacarpals and coccigea vertebrae of pigs that received higher Zn supplementation in diet. Studies comparing organic and inorganic sources of Cu showed an increased uptake and retention of Cu in pigs fed organic source (Coffey et al 1994, Veum et al 2004), which was not observed in the present study for Fe, Cu, and Zn content in bones.…”
Section: Mineral Retention In Metacarpals and Livercontrasting
confidence: 86%
“…Feeding lower concentrations of organic Zn greatly decreased the amount of Zn excreted in comparison with inorganic Zn, without loss of growth performance. Veum et al (2004) studied a Cu proteinate in weaned pigs in comparison with inorganic Cu sulfate. Piglet performance was consistently better with organic Cu at 50 to 100 ppm, in comparison with inorganic Cu at 250 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…AlĂ©m disso, pesquisas tĂȘm demonstrado redução da presença de cobre na cama em 74% (MANANGI, 2012), e 75% (BAO et al, 2009) com o uso das fontes orgĂąni-cas de cobre, quando comparado com as fontes inorgĂąnicas. Veum et al (2004) relataram que algumas fontes de proteinato de cobre demonstraram efeito superior ao sulfato, absorvendo e retendo mais cobre e, excretando menos quantidade do mineral nas fezes de leitĂ”es. Animais que receberam nĂ­veis de 50 e 100 mg/kg de proteinato de cobre excretaram respectivamente 77 e 61% menos os animais que receberam 250 mg/kg de sulfato de cobre.…”
Section: Issn: 1982-1131unclassified